Influence of direct and metaphorical meanings in the legal norms (Journal of Oriental Studies, 2017)
This article discusses the features of the application of direct and metaphoricalmeanings in religious texts and describes their impact on changingrules of law. And also will address the study of the Hanafi legal schoolof metaphorical meanings in linguistic and semantic and legal directions